GAMBARAN STRATEGI PROMOSI KESEHATAN DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN KEJADIAN STUNTING DI KABUPATEN GIANYAR - Mirah Anjani, Ni Luh Kadek; Wulandari, Luh Putu Lila (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p16, 2025)
Stunting or short is one form of lack of nutritional intake that occurs in children. Gianyar Regency has succeeded in reducing the incidence of stunting which is quite rapid from 2018-2021. This study aims to determine how the description of health promotion strategies that have been carried out by Gianyar district in accelerating stunting reduction. This study used descriptive qualitative research method. Data were obtained through in-depth interviews and FGDs. The informant retrieval technique carried out was purposive sampling with a total of 21 people. The research was conducted at Puskesmas Blahbatuh 2 and Puskesmas Payangan. The results showed that Gianyar Regency uses health promotion strategies in the form of, Advocacy that there are policies that are used as a reference in advocating for policy holders, community empowerment with counseling methods, KIE, role play, cadre empowerment and there are different innovations owned by the two puskesmas, namely, “ Si Sadar Jaje Uli” and “Nobardisi”. In carrying out health promotion, the two puskesmas use media in the form of posters, leafts and flipcharts as well as providing education through social media. Social support is carried out through PKK mothers, political figures and families. The health promotion strategy carried out by Gianyar Regency is the same but what distinguishes it is in how to run it and there are supporting and inhibiting factors. Keywords: Health Promotion, Stunting, Community Empowerment, Social Support, Advocacy, Gianyar Regency, Bali